Sistem Kekerabatan dalam novel Hong Lou Meng karya Cao Xueqin: Analisis Sosiologi Sastra - Sheyra Silvia Siregar (Jurnal Bahasa dan Sastra, 2021)
This study describes the kinship system adhered to by the people of East Asia, especially the People's Republic of China. The rich and diverse kinship system is clearly illustrated and applied in a large family during the dynastic kingdom in China. The purpose of this study was to identify and describe the kinship system in Hong Lou Meng novel by Cao Xueqin. In addition, this novel also tells about a family that contains many different kinship systems. This research belongs to a descriptive-qualitative perspective. The results of the analysis show an overview of the kinship system contained in a large family in Ancient China about the Chinese ethnic kinship system in the past through Hong Lou Meng novel by Cao Xueqin.